COA6 Facilitates Cytochrome c Oxidase Biogenesis as Thiol-reductase for Copper Metallochaperones in Mitochondria. Issue 7 (27th March 2020) - Pacheu-Grau, David; Wasilewski, Michał; Oeljeklaus, Silke; Gibhardt, Christine Silvia; Aich, Abhishek; Chudenkova, Margarita; Dennerlein, Sven; Deckers, Markus; Bogeski, Ivan; Warscheid, Bettina; Chacinska, Agnieszka; Rehling, Peter
Abstract: The mitochondrial cytochrome c oxidase, the terminal enzyme of the respiratory chain, contains heme and copper centers for electron transfer. The conserved COX2 subunit contains the CuA site, a binuclear copper center. The copper chaperones SCO1, SCO2, and COA6, are required for CuA center formation. Loss of function of these chaperones and the concomitant cytochrome c oxidase deficiency cause severe human disorders. Here we analyzed the molecular function of COA6 and the consequences of COA6 deficiency for mitochondria. Our analyses show that loss of COA6 causes combined complex I and complex IV deficiency and impacts membrane potential-driven protein transport across the inner membrane. We demonstrate that COA6 acts as a thiol-reductase to reduce disulfide bridges of critical cysteine residues in SCO1 and SCO2. Cysteines within the CX3 CXN H domain of SCO2 mediate its interaction with COA6 but are dispensable for SCO2–SCO1 interaction. Our analyses define COA6 as thiol-reductase, which is essential for CuA biogenesis. Graphical abstract: Image 1 Highlights: Loss of COA6 affects respiratory chain complexes IV and I. Decreased membrane potential-driven protein import due to loss of COA6. Cysteine residues in the CX3 CXN H motif of SCO2 mediate COA6 interaction. COA6 acts as thiol reductase for copper metallochaperones during CuA biogenesis.